Analisis senyawa acetaminophen dalam sampel biologis dengan berbagai macam metode - Lina Nurfadhila; Marsah Rahmawati; Nur Komala fitri; Salsabila Granadha Nibullah; Welly Windari (Journal of Pharmaceutical and Sciences, 2023)
Acetaminophen or Paracetamol is a compound that has pharmacological effects as an analgesic and antipyretic. The purpose of this journal review is to identify and understand the various methods that can be used to analyze biological samples of patients when taking paracetamol through their biological samples. The initial process for carrying out the analysis is to carry out sample preparation, samples are prepared by various suitable methods such as liquid-liquid extraction methods, solid phase extraction (SPE) and protein precipitation methods, then samples will be analyzed using appropriate methods. instruments such as GC-MS, LLE, LC-MS, HPLC-MS, or UHPLC-MS. Of the several instruments used the HPLC-MS method is the most effective method for analyzing biological samples, because HPLC-MS is considered fast, selective and sensitive and has the lowest LLOQ quantification value or lower limit.